IMPLEMENTASI MANAJEMEN PENDIDIKAN ISLAM DALAM PENGELOLAAN GURU DAN SISWA DI MADRASAH ALIYAH NEGERI 1 MAJENE - Nurhikmah Nurhikmah; Ahmad Fathul; Muhammad Faqi; Asdar Asdar; Kamus Kamus; Nurauliah Nurauliah (Jurnal Manajemen Pendidikan, 2026)
Article aims to analyze the implementation of Islamic education management in the management of teachers and students at Madrasah Aliyah Negeri 1 Majene and to identify the obstacles encountered in its implementation. Using a qualitative approach with a descriptive design, the data were collected through interviews, observations, and documentation involving the vice principal, teachers, and students. The data were then analyzed through the processes of data reduction, data presentation, and conclusion drawing. The findings reveal that teacher management was implemented through program evaluation, supervision, competency development, training, religious habituation, and task distribution. Meanwhile, student management was carried out through religious activities such as moral development, dhuha prayer, Qur’anic recitation, tahfidz, religious speeches, and Ramadan safari programs. The obstacles identified include differences in students’ educational backgrounds, limited basic religious understanding, time constraints, and the discipline of teachers and students in participating in religious activities. The novelty of this study lies in its comprehensive mapping of the implementation of Islamic education management in madrasahs, highlighting both management strategies and practical challenges. Therefore, this study contributes to understanding the effectiveness of Islamic education management in creating a religious and well-directed educational environment in accordance with the goals of Islamic education.